Entre a contemplação e a vida ativa: a mística intramundana em Thomas Merton - Rizzo, Adriel de Oliveira (2025)
This paper analyzes Thomas Merton's intramundane mysticism with a focus on his work New Seeds of Contemplation. The aim was to explore how Merton's integrative vision between contemplation and active life offers significant contributions to the study of contemporary mysticism in the field of Religious Science. The central hypothesis is that Merton's works and the studies of his thought are relevant to the understanding of contemporary religion, especially in the studies produced by the Science of Religion in Brazil. In this context, through an in-depth analysis of Merton's main works, the work explored the fundamental concepts that underpin intramundane mysticism, showing how this vision was concretized not only in his writings, but also in his life. It also examined Merton's biographical and intellectual development, contextualized his major writings, and analyzed the development of his thinking on the relationship between the contemplative and the active life. It also explored his particular conception of mysticism and monastic life, with particular attention to the concept of “Le Point Vierge”. Finally, we analyzed how Merton articulates the relationship between mysticism and social engagement. It was concluded that Merton's approach, which deeply integrates the contemplative life and the active life, offers a valuable paradigm for rethinking the relationship between spirituality and social action in the contemporary context and makes a significant contribution to studies of contemporary mysticism